2022
DOI: 10.1007/s12144-022-03012-2
|View full text |Cite|
|
Sign up to set email alerts
|

Testing an Online Program to Foster Need Crafting During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic represents a threat not only to individuals’ physical health but also to their mental health. Self-Determination Theory assumes that the satisfaction of basic psychological needs for autonomy, relatedness and competence promotes psychological well-being during destabilizing times. Yet, the pandemic seriously hampered individuals’ opportunities to satisfy their needs. The current study provides a preliminary test of the effectiveness of a 7-session online program, LifeCraft, that promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…For instance, Behzadnia and FatahModares (2020) showed that students who followed an intervention on how to support their own needs reported higher need fulfillment, more vitality, and less test anxiety across time. Similarly, Laporte et al (2022) showed that an intervention targeting need crafting was effective in increasing adults' need crafting during the COVID-19 crisis, at least when people were sufficiently engaged during the intervention. In turn, need crafting was related to more need fulfillment and better mental health.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, Behzadnia and FatahModares (2020) showed that students who followed an intervention on how to support their own needs reported higher need fulfillment, more vitality, and less test anxiety across time. Similarly, Laporte et al (2022) showed that an intervention targeting need crafting was effective in increasing adults' need crafting during the COVID-19 crisis, at least when people were sufficiently engaged during the intervention. In turn, need crafting was related to more need fulfillment and better mental health.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 97%
“…Examining these dynamics within and across different levels of analysis has both theoretical and applied value, because experiences of need satisfaction are susceptible to change and can be targeted through interventions or counseling (e.g. Laporte et al, 2022).…”
Section: Present Researchmentioning
confidence: 99%
“…The brief reporting of the findings in the media helped the population to contextualize their concerns, motivations, and behavior. Also, through opinion pieces and media interventions, we informed the population that the pursuit of need-satisfying activities is a proactive pathway to preserve one's wellbeing and to experience a sense of meaning in distressing times (Laporte et al, 2021(Laporte et al, , 2022. Other opinion pieces addressed the role of motivation and how policymakers could develop a narrative and communication style that supports the long-term commitment of the population (Pope et al, 2018).…”
Section: Population and Intermediate Organizationsmentioning
confidence: 99%
“…Further, in terms of methodology , the Motivation Barometer relied on a variety of research designs and statistical methods to collect and analyze findings. We used both cross‐sectional cohorts (e.g., Van Oost et al., 2022) and longitudinal follow‐up surveys (e.g., Waterschoot, Van Oost, Vansteenkiste et al., 2023), but also administered experimental designs in both a vignette format (e.g., Morbée, Waterschoot, et al., 2022) and in real‐life intervention studies (e.g., Laporte et al., 2022).…”
Section: Part 1: Description Of the Motivation Barometermentioning
confidence: 99%
See 1 more Smart Citation